Simulation and measurement of ferromagnetic impurities in non-magnetic aeroengine turbine disks using fluxgate magnetometers. (November 2015) - Hantscher, Sebastian; Zhou, Ruixin; Seidl, Albert; Hinken, Johann; Ziep, Christian
Abstract: In this paper, ferromagnetic impurities in paramagnetic aeroengine turbine disks are investigated. Because such inclusions represent a significant threat in aviation, a detailed analysis is required for impured turbine disks. For this purpose, sensitive fluxgate magnetometers are used. After a premagnetisation, this sensor is able to detect small ferromagnetic particles by recording the variation of the magnetic flux density while the disk rotates below the sensor head. This trajectory creates a unique signature. However, the measured signatures are often distorted. A main reason for these distortions is that the particles are not oriented in axial direction (in the direction of the disks axis). Up to now, it was not possible to interpret the measured signatures. Thus, a simulation tool has been developed that provides a catalogue of different magnetic flux density distributions of typical orientations, positions and various distances to the fluxgate magnetometer position. For these simulations, the particles are assumed to be dipoles. As part of impurities are not caused by concentrated particles but by elongated ones, so-called or dipole lines, the model has been expanded for these cases by using numerical integration techniques. Measurements verify the assumption to approximate impurities by dipoles.